2007
DOI: 10.1021/la700650q
|View full text |Cite
|
Sign up to set email alerts
|

Nano/Microscale Order Affects the Early Stages of Biofilm Formation on Metal Surfaces

Abstract: The adhesion of Pseudomonas fluorescens was studied on nano/microengineered surfaces. Results show that these bacteria formed well-defined aggregates on randomly oriented nanosized granular gold substrates. These aggregates consist of aligned ensembles of bacteria, with some of them strongly elongated. This kind of biological structure was not found on ordered engineered surfaces because bacterial alignment and cell-to-cell sticking were hindered. Importantly, differences in cell morphology, length, orientatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 124 publications
(111 citation statements)
references
References 48 publications
8
100
0
1
Order By: Relevance
“…Mechanisms underpinning attachment to nanoscale topographies for mammalian cells is a greatly studied area which has continued to foster significant findings and major contributions to the wealth of knowledge on eukaryotic cell behavior [82][83][84][85]. However, as Hsu et al [48] have described, attachment phenomena for bacterial cells at the nanoscale is less understood, as relatively few reported works have explored the effects of nanoscale topography on bacterial attachment behavior and biofilm formation [23,49,54,86,87]. In fact, some work on bacterial attachment to nanoscale topography resulted in a higher degree of attachment to nanoscaled surfaces rather than planar or micron-scaled topography [88][89][90][91].…”
Section: Pushing Antifouling Topography To the Nanoscalementioning
confidence: 99%
See 1 more Smart Citation
“…Mechanisms underpinning attachment to nanoscale topographies for mammalian cells is a greatly studied area which has continued to foster significant findings and major contributions to the wealth of knowledge on eukaryotic cell behavior [82][83][84][85]. However, as Hsu et al [48] have described, attachment phenomena for bacterial cells at the nanoscale is less understood, as relatively few reported works have explored the effects of nanoscale topography on bacterial attachment behavior and biofilm formation [23,49,54,86,87]. In fact, some work on bacterial attachment to nanoscale topography resulted in a higher degree of attachment to nanoscaled surfaces rather than planar or micron-scaled topography [88][89][90][91].…”
Section: Pushing Antifouling Topography To the Nanoscalementioning
confidence: 99%
“…Thus, in the presence of topographical features, they are not easily deformed (as mammalian cells would typically be) [7]. Instead, bacterial appendages are both small and relatively flexible, enabling them to probe nanoscale features [54,86,87]. Thus, these extracellular appendages could play a crucial role in attachment to surface features much smaller than the dimensions of the cells themselves.…”
Section: Pushing Antifouling Topography To the Nanoscalementioning
confidence: 99%
“…Webster and colleagues (2005) concluded that nanophase alumina and associated cast polymer surfaces had signifi cantly higher bacterial (Pseudomonas fl uorescens) adhesion than conventional surfaces of the same material. Pseudomonas fl uorescens morphology, length, orientation, and fl agellation differed between bacteria attached on ordered nano-or microstructures and randomly ordered surfaces (Diaz et al 2007). Although there is evidence that bacterial attachment is altered on nanophase surfaces, the mechanism behind this phenomenon as well as bacterial metabolism differences remain unclear.…”
Section: Introductionmentioning
confidence: 99%
“…In this sense, it had demonstrated the major role of surface nanotopography in bacterial adhesion and biofilm formation [15][16][17]50] . Different studies using modeled nanostructured surfaces have demonstrated the influence of the nanostructure in the inhibition of bacterial adhesion [18,51,52] . Nature constitutes an unexhausted font of inspiration for scientists and engineers, particularly in biomimetics [13] .…”
Section: Development Of Nanostructured Surfacesmentioning
confidence: 99%
“…On the other hand, it has been demonstrated that surface nanotopography and architecture plays an essential role in bacterial attachment and biofilm formation [12][13][14][15] . In fact, Campoccia et al [16] indicated that the use of nanostructured surfaces with inhibited bacterial adhesion could represent a challenging alternative to antibiotics [17][18][19] . Varied surface modification techniques have been widely used in the fabrication of artificial antibacterial surfaces [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%